Preventive and remedial measures to combat financial and administrative corruption An analytical study from an Islamic perspective - کارزان فقي خليل كريم (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
Corruption means misuse of public funds, behavior contrary to laws and morals, and violation of public interests, through the exploitation of public money and its use illegally to achieve special interests. Corruption may be systematic, may be irregular behavioral disorder, and may in some forms amount to criminal crime: bribery, money laundering, embezzlement, fraud, forgery, etc. The research clarifies the financial and administrative corruption in the Holy Quran and the prophetic Hadith, and the interest of Islam in this serious problem. It also sheds light on the legal and administrative reasons that lead to the spread of financial and administrative corruption in the world, especially in the developing countries, then the political reasons, the social reasons, the economic reasons, and the absence of religion. The research provides preventive and curative measures to combat financial and administrative corruption from an Islamic perspective, including: employing the Secretariat in jobs and jobs, and placing the appropriate employee in the right place. Finally, the study highlights the most important findings and recommendations.